A Study on the Adjustment to College Life of Freshman - Min, Shinhong; Yun, Soonyoung (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: The purpose of this study is to use it as a basic data for arbitration development to increase the adaptability of freshmen to college life through the survey of freshmen’s college students. Methods/Statistical analysis: The survey was conducted and analyzed on 160 new students on their university life adaptation, including academic adaptation, social adaptation, emotional adaptation, physical adaptation and attachment to college. Findings: First of all, the degree of adaptation to college life depends on what level of study you think, major satisfaction, admission type, interest in your major, financial burden, whether you think about dropping out or not, and whether you think about taking a leave of school. Improvements/Applications: We have found that student counseling, development and operation of guidance-related programs and institutional support are needed to help college freshmen succeed in their college life, and various follow-up studies are needed to study the effects after application.